Hak Anak di Atas Kertas: Kegagalan Negara dalam Pemenuhan Pendidikan Dasar di Wilayah 3T: Analisis Sosiologi Hukum (Studi Kasus di Sumba) - Bruno Bani; Novinda Grezen Nufninu (Universitas Sains dan Teknologi Komputer, 2026)
This research is motivated by the ongoing disparity in the distribution of education in underdeveloped, frontier, and outermost regions (3T), particularly in the Sumba region, despite national regulations and commitments to education funding being established. The main issue lies in the gap between legal norms that guarantee equal access to education and the reality of its implementation at the regional level. This research aims to analyze the effectiveness of educational equity policies from the perspective of legal sociology and to identify the structural factors that influence their implementation. The research method used is a qualitative approach with a case study design. Data were obtained through interviews with 30 informants consisting of education officials, school principals, teachers, and parents, as well as supported by document analysis and secondary data. The research results indicate that the education equity policy has not been fully effective, marked by an imbalance in the teacher-student ratio, limited infrastructure, and resource distribution constraints. These findings indicate a gap between regulatory design and implementation practices, influenced by institutional capacity, intergovernmental coordination, and the geographical conditions of the region. Theoretically, this research reinforces the perspective that the effectiveness of law is determined by the interaction between norms, structures, and social conditions. Practically, this research recommends need-based affirmative policies to achieve substantive educational equity in the 3T areas.